2021
DOI: 10.3389/fonc.2021.636870
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 and CD3E as Indicators for Tumor Microenvironment Modulation in Bladder Cancer and Their Correlations With Immune Infiltration and Molecular Subtypes

Abstract: Bladder cancer (BLCA) represents the ninth most common malignant tumor in the world and is characterized by high recurrence risk. Tumor microenvironment (TME) plays an important role in regulating the progression of BLCA. Immunotherapy, including Bacillus Calmette-Guerin (BCG) and programmed cell death protein 1 (PD-1)/programmed death ligand 1 (PD-L1), is closely associated with TME and is widely used for treating BLCA. But parts of BLCA patients have no response to these treatment ways, thus a better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Blocking this axis seems to be a relevant strategy for BCa treatment as SDF-1 and CXCR4 are expressed in bladder tumor tissue [ 143 ]. Their expression is associated with tumor pT stage and grade [ 144 , 145 , 146 ] but also with poor patient OS [ 147 ]. Moreover, TCGA analysis demonstrated that SDF-1 gene expression positively correlates with M2-like TAMs [ 146 ], confirming the relationship between the SDF-1-CXCR4 axis and TAM recruitment in BCa.…”
Section: Targeting Tams To Improve Bladder Cancer Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Blocking this axis seems to be a relevant strategy for BCa treatment as SDF-1 and CXCR4 are expressed in bladder tumor tissue [ 143 ]. Their expression is associated with tumor pT stage and grade [ 144 , 145 , 146 ] but also with poor patient OS [ 147 ]. Moreover, TCGA analysis demonstrated that SDF-1 gene expression positively correlates with M2-like TAMs [ 146 ], confirming the relationship between the SDF-1-CXCR4 axis and TAM recruitment in BCa.…”
Section: Targeting Tams To Improve Bladder Cancer Outcomementioning
confidence: 99%
“…Their expression is associated with tumor pT stage and grade [ 144 , 145 , 146 ] but also with poor patient OS [ 147 ]. Moreover, TCGA analysis demonstrated that SDF-1 gene expression positively correlates with M2-like TAMs [ 146 ], confirming the relationship between the SDF-1-CXCR4 axis and TAM recruitment in BCa. Despite that, no preclinical study has evaluated the effect of blocking TAMs via the SDF-1-CXCR4 pathway in BCa.…”
Section: Targeting Tams To Improve Bladder Cancer Outcomementioning
confidence: 99%
“…However, whether the TME status of BLCA contributes to the prediction of BLCA prognosis remains unknown. Recent studies have been reported that the immune and stromal scores in the TME could be calculated by ESTIMATE algorithms, which contributes to provide a novel insight into the development of immune treatment ( 21 ). Currently, immunotherapy for TME has been shown to improve BLCA treatment ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CCR5 therapy in cancer patients can effectively target tumor immune cells in colorectal cancer metastasis ( Jiao et al, 2019 ). As an indicator of bladder cancer TME regulation, CD3E is closely related to immune infiltration ( Liu Y. et al, 2021 ). The tumor antigen-specific CD4 + T cells in cancer immunity are a key strategy for tumor prognosis and treatment ( Protti et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%